Challenging Military Court Jurisdiction Over Corruption Cases After Criminal Law Enforcement - Suartini Suartini; Rijal Ibnu Sani (Indonesian Journal of Law and Policy Studies, 2025)
The main issue in this research is the dualism of absolute jurisdiction in handling corruption cases involving Indonesian National Armed Forces personnel. Although the anti-corruption legal framework forms a unified lex specialis system, such cases are often tried in Military Courts, which lack key instruments like investigations by the Corruption Eradication Commission and Ad Hoc Corruption Judges. This study aims to challenge the procedural legality of Military Courts in adjudicating corruption cases and highlights the need to unify corruption adjudication. Using normative legal research with statutory and conceptual approaches, it identifies conflicts between Military Court Law and national anti-corruption laws. The findings show that the absence of specific anti-corruption mechanisms in the military leads to procedurally flawed decisions and violates equality before the law. Therefore, all corruption cases should be handled by the Corruption Court as a single forum. Referring to Article 65(2) of the Indonesian National Armed Forces Law, soldiers must be subject to general courts for general crimes, including corruption. Thus, jurisdictional unification is essential to ensure legal certainty, transparency, and effective anti-corruption enforcement in Indonesia.